Praktek Penyaluran Kembali Sewa Menyewa TV Kabel - Fadlan Azima Harahap (Jurnal El-Thawalib, 2022)
This study discusses the Compilation Review of Sharia Economic Law on the Practice of Redistributing Cable Tv Rentals in Tobu Village, North Padangsidimpuan Village, Padangsidimpuan City. This research is motivated by the use of rented goods that are not in accordance with the provisions of Sharia Economic Law (KHES) due to the tenant misusing the rented goods into provisions that have been prohibited according to Islamic Shari'a. As for the formulation of the problem in this study, how is the practice of redistribution of cable tv rental in Tobu Village, North Padangsidimpuan Village, Padangsidimpuan City and how is the Sharia Economic Law Compilation Perspective on the practice of redistribution of cable TV rental in Tobu Village, North Padangsidimpuan Village, Padangsidimpuan City. Based on the formulation of the problem, the purpose of this study is to find out the practice of redistribution of cable tv rental in Tobu Village, North Padangsidimpuan Village, Padangsidimpuan City and to find out how the Sharia Economic Law Compilation Perspective is on the practice of redistributing cable TV rental in Tobu Village, North Padangsidimpuan Village, Padangsidimpuan City. .This study uses qualitative research that seeks to describe, describe a situation and event based on the facts that occur in the field to obtain conclusions. As for the subject in this study, the tenants use rented goods to the road which clearly contradicts the provisions of KHES in article 310. Then the data collection technique in this study uses snowball sampling techniques using interviews, observations to Cable TV tenants and TV employees. Cable. The results of this study indicate that the practice of redistributing cable tv rental in Tobu Village is not in accordance with the provisions of the Sharia Economic Law Compilation in article 310 because the tenant has made the rental without the knowledge of the owner, which in essence the practice is not allowed according to Islamic law and the provisions of the Legal Compilation. Sharia Economics.